2020
DOI: 10.18502/tbj.v19i1.2815
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Depression Based on Cognitive Emotion Regulation Strategies

Abstract: Introduction: In recent years, many studies focused on emotion regulation in conceptualization, explanation, and treatment of mental disorders. Problematic patterns of emotional reactivity and regulation are prominent factors in various mental disorders, specially internalizing disorders. The present study aimed to identify the role of emotion regulation strategies in predicting depression. Method: This descriptive –correlational research was conducted on 650 students of Yazd University selected by clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The present study has a negative and significant correlation between adjusted emotion regulation strategies such as positive refocusing, positive appraisal, and putting into perspective. Dadfarnia et al (7) reported an inverse and significant relation between adjusted emotion regulation strategies such as acceptance, positive refocusing, planning, and putting into perspective, which was consistent with this study. These strategies lead to the higher flexibility of the person towards encountering different conditions, experiencing a lower level of depression.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present study has a negative and significant correlation between adjusted emotion regulation strategies such as positive refocusing, positive appraisal, and putting into perspective. Dadfarnia et al (7) reported an inverse and significant relation between adjusted emotion regulation strategies such as acceptance, positive refocusing, planning, and putting into perspective, which was consistent with this study. These strategies lead to the higher flexibility of the person towards encountering different conditions, experiencing a lower level of depression.…”
Section: Discussionsupporting
confidence: 92%
“…Dadfarnia et al studied the Yazd students and showed this relationship (7). In addition, Dadfarnia et al's study demonstrated a relationship between rumination and other blame with depression (7). Martin and Dahlen observed a significant positive relationship between catastrophizing and depression (16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations